Application of sodium percarbonate activated with Fe(II) for mitigating ultrafiltration membrane fouling by natural organic matter in drinking water treatment. (1st October 2020) - Li, Peijie; Cheng, Xiaoxiang; Zhou, Weiwei; Luo, Congwei; Tan, Fengxun; Ren, Zixiao; Zheng, Lu; Zhu, Xuewu; Wu, Daoji
Abstract: It remains challenging to efficiently mitigate membrane fouling caused by natural organic matter (NOM) for the widespread application of ultrafiltration process. In this study, sodium percarbonate activated with Fe(II) (Fe(II)/SPC) was proposed as a feedwater pretreatment strategy for membrane fouling control. Typical NOM fractions, i.e., humic acid (HA), bovine serum albumin (BSA) were employed as membrane foulants, as well as natural surface water. The results showed that Fe(II)/SPC pretreatment apparently alleviated membrane fouling by BSA and HA-BSA, and the performance outperformed Fe(II) pre-coagulation and SPC pre-oxidation alone. Considering HA fouling, more severe flux decline and increased reversible fouling resistance were obtained, while irreversible fouling was slightly mitigated. The filtration of HA-BSA was well fitted to intermediate blocking followed by cake filtration, and Fe(II)/SPC noticeably increased the filtration volume corresponding to the formation of cake filtration. With Fe(II)/SPC pretreatment, a sparser and more homogeneous foulant layer with lower resistances was observed on membrane surface, and Fourier transform infrared spectroscopy indicated that the peak intensities of major functional groups for organic pollutants were significantly decreased. In surface water treatment, Fe(II)/SPC could effectively improve membrane filtration behavior and pollutants removal, with a distinct decrease of both fluorescent fractions and different molecular weight organic compounds. It seemed that hydroxyl radical oxidation and coagulation with in-situ formed Fe(III) were the main mechanisms of contaminants removal and membrane fouling control. Overall, this combined process exhibited a great potential for actual application during drinking water treatment. Graphical abstract: Image 1 Highlights: Ferrous ion/sodium percarbonate (Fe(II)/SPC) was used for membrane fouling control. Fe(II)/SPC showed better membrane fouling control effect than Fe(II) and SPC alone. The fouling control efficiency was influenced by the fraction of organic matter. Fe(II)/SPC has a potential application prospect in natural surface water treatment.